English to Sign Language (E2SL): A Tool to Assist Hearing Impaired Students to Learn Computer Terminologies - Alhasan, Anas Mahmoud Ali (2010)
This research aimed to understand the hearing impaired students' needs. A prototype tool was designed to assist hearing impaired students in learning about computer terminologies. The prototype works as a dictionary to translate computer terminologies from English text to American Sign Language format. This tool provides definition and related information about each terminology. Illustrated pictures, video, and voice will be used to help users to better understand and be familiar with computer terminologies. The terminologies translated to specific signs where every terminology has a unique sequence of signs that make it easier for children to recognize and learn. Also, the system provides a pronunciation example for each terminology because some of disabled students may only have mild a hearing impaired problem. This may help these students to learn the correctly pronunciation of the computer terminologies. At same time, the system provides a related video to help the students to understand the terminologies. Since the end users of this prototype are children who are hearing impaired, the tool was developed to be easy to use and without long training durations.